Ways to improve social skills in primary school students based on socio-legal norms - Abdullayeva Maryambibi Djumaniyazovna (Periodica Journal, 2022)
In this article, we will talk about primary school students with social subjects to understand exactly what rules of conduct they must follow in a relationship, it has been highlighted the ways in which they are required to be aware of the types of social norms
Keywords: rules of conduct; resources; aesthetic norms; standards of activity